1996
DOI: 10.1088/0143-0807/17/4/001
|View full text |Cite
|
Sign up to set email alerts
|

The historical burden on scientific knowledge

Abstract: The development of scientific knowledge is compared with the evolution of biological systems. Just as every biological system inevitably contains fossils our physics syllabus contains obsolete concepts and methods. It is argued that the potential for simplifying the teaching of science by eliminating these historical burden is high. Several examples for obsolete concepts in physics are given. Zusammenfassung Die Entwicklung der Inhalte des wissenschaftlichen Lehrgebäudes wird mit der Evolution biologischer Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The enrichment of Fe(III) ions leads to the increase of the chemical potential. The chemical potential can be expressed [31] as u = ∂ G ∂ n , which is the change of Gibbs free energy when the change of the amount of components is 1 mol. Since each of the components in the solution is Fe(III) ions, the chemical potential can be written as…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment of Fe(III) ions leads to the increase of the chemical potential. The chemical potential can be expressed [31] as u = ∂ G ∂ n , which is the change of Gibbs free energy when the change of the amount of components is 1 mol. Since each of the components in the solution is Fe(III) ions, the chemical potential can be written as…”
Section: Resultsmentioning
confidence: 99%
“…However, this is a very stringent condition in a real laboratory, since any changes would have to be performed in a very good vacuum. 12 Sometimes students are even given linear plots of stopping potential for sodium, which purport to be Millikan's original data, and are asked to calculate the work function. However these plots have usually been arranged to have an intercept of 2.3 eV, which is the value reported for sodium in many compilations, but clearly cannot be a real result since Millikan had a collector of oxidised copper, with a work function greater than 5 eV.…”
Section: Consequences Of the Errormentioning
confidence: 99%
“…is retained. However, for the determination of the Planck constant, an 12 In one of the papers on this topic [8], it was suggested that a photoemission device should be manufactured in which emission from several different surfaces could be examined. With this, students could see for themselves that the same line is generated.…”
Section: Consequences Of the Errormentioning
confidence: 99%
See 1 more Smart Citation
“…Some time ago, it has been advocated that scientific knowledge has generated during its rapid expansion a certain number of conceptual fossils. 1 Among the identified fossils we have: Newton's three laws, actions at distance in physics, existence of several forms of energy, space 'full of nothing' but having properties, hysteresis curves in ferromagnetism and entropy as a measure of disorder. It is worth noting that such fossils exist because they are vestiges of ways of thinking that are no more adapted to modern scientific knowledge.…”
Section: Introductionmentioning
confidence: 99%